KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DALAM MATERI HIMPUNAN DI KELAS VII SMP NEGERI 7 KUBU RAYA - Dianti, Wulan; Zubaidah, Zubaidah; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed to describe the students’ mathematical communication ability to solve questions of sets in 7th grade of SMP Negeri 7 Kubu Raya. The research method was descriptive and research design was survey. The subject of this research was students of class VII A ofSMP Negeri 7 Kubu Raya. The subject was choosen based on teacher’s recommendation. The research used quetions to know the students’ mathematical communication ability. There were two questions and each questions had one of two indicators of mathematical communication ability.The result of this study indicate that students mathematical communication skill obtained of 55%. This can be seen based on indicators of mathematical communication ability students’ mathematical communication ability in expressing problem into Venn’s diagram or notation of sets was 20% and it was categorized as very low and students’ mathematical communication ability in interpretation of problem into mathematics model or Venn’s diagram was 90% and it is categorized as very high. Keywords: Sets, Mathematical Communication,Mathematical Communication Ability